Rare disease genomics and precision medicine - Juhyeon Hong; Dajun Lee; Ayoung Hwang; Taekeun Kim; Hong-Yeoul Ryu; Jungmin Choi (Genomics & Informatics)
Abstract Rare diseases, though individually uncommon, collectively affect millions worldwide. Genomic technologies and big data analytics have revolutionized diagnosing and understanding these conditions. This review explores the role of genomics in rare disease research, the impact of large consortium initiatives, advancements in extensive data analysis, the integration of artificial intelligence (AI) and machine learning (ML), and the therapeutic implications in precision medicine. We also discuss the challenges of data sharing and privacy concerns, emphasizing the need for collaborative efforts and secure data practices to advance rare disease research.